Stable Isotope Analysis of Dermis and the Foraging Behavior of Whale Sharks at Ningaloo Reef, Western Australia - Marcus, Lara; Virtue, Patti; Nichols, Peter D.; Ferreira, Luciana C.; Pethybridge, Heidi; Meekan, Mark G. (Frontiers in Marine Science, 2019)
Stable isotope analysis of dermis was used to examine foraging behavior of whale sharks at Ningaloo Reef in Western Australia. Values of δ13C and δ15N in dermis were compared to those obtained from likely species of local prey. The δ13C values of zooplankton and nektonic taxa at Ningaloo ranged from −18.9‰ to −16.5‰ reflecting the different carbon sources (from pelagic to more inshore and benthic) entering the food web. Isotopic values also varied depending on the diet-to-tissue discrimination factor applied in the analysis. When data was corrected using factors derived from slow turnover, structural cartilage in fins, whale sharks showed a greater reliance on pelagic food webs, whereas analyses using raw data suggested a greater dietary component from benthic and inshore habitats. Variability in δ15N values (6.9‰ to 10.8‰) implied different patterns of foraging among whale sharks, likely indicating movement among foraging localities that occur at Ningaloo Reef and along the Western Australian coast. There was evidence of enrichment in 15N occurring with increasing size in males and females, a pattern that could have been due to changes in growth rate and trophic level with age and/or an ontogenetic shift in feeding grounds. Given the variability potentially induced in stable isotope values by differences in rates of turnover of tissues and the use of diet-to-tissue discrimination factors, future studies would benefit from a multi-technique approach using different tissues to identify the diet of whale sharks.